Capoeira sou eu: memória, identidade, tradição e conflito - Fonseca, Vivian Luiz (2009)
The purpose of this research is to analise how the conflict of tradition in caporeira occurs, specially from the creation of the two groups Angola and Regional in the 1930s. The disputes concerning the memory that takes place among the existing groups, as an attempt to legitimize as the true capoeira, are also important in this study. Through this reseach, we try to understand how the mestres (masters) of capoeira build up and restore the past. Besides this, it analises the way the memories are articulated so that to give meaning to its current posture and also determining the identity boundaries of the organized groups. For this research, the mestres knowledge and their world vision were the base to understand deeply the world of capoeira and perceive the current issues concerning these social individuals. The methodology used in the work as well as the main procedure to get all the sources of data was the oral history.